Morphological and Molecular Identification of Dactylonectria macrodidyma as Causal Agent of a Severe Prunus lusitanica Dieback in Italy - Susanna Pecchia; Benedetta Caggiano; Daniele Da Lio; Emilio Resta (Horticulturae, 2023)
During the summer of 2016, severe dieback was observed on young potted Prunus lusitanica (Portugal laurel) plants in a nursery in the Pistoia province (Tuscany, Italy). Cylindrocarpon-like isolates were consistently recovered from diseased plant tissues. The combination of morphological and molecular traits, including sequence data of histone 3 and β-tubulin genes (HIS3, TUB2) and internal transcribed spacers (ITS), allowed the identification of Dactylonectria macrodidyma (Halleen, Schroers & Crous) L. Lombard & Crous (asexual form Cylindrocarpon macrodidymum) as the causal agent of the disease. Pathogenicity tests reproduced disease symptoms observed in the nursery after six months fulfilling Koch’s postulates. D. macrodidyma is a soilborne plant pathogen and is to be considered of great economic importance on P. lusitanica, especially under favorable conditions such as stress and/or reduction of plant vitality. The increasingly frequent reports of the disease caused by the pathogen in various nurseries suggest that pot cultivation, together with prolonged drought periods, may play a role in favoring infections. To the best of our knowledge, this is the first report worldwide of the occurrence of dieback on Prunus lusitanica caused by D. macrodidyma.